THE FACTORS EFFECTING FIRM VALUE EVIDENCE FROM INDONESIA - Supriliana, Ni Gusti Ayu Komang Tri; Wijaya, Henryanto (International Journal of Application on Economics and Business, 2025)
This study aims to measure the simultaneous and partial impact of Earnings Quality, Tangible Assets, and Leverage on Firm Value in real estate and property companies based on the Indonesia Stock Exchange (IDX) 2021-2023 as a limitation field. This study uses a data processing method with the EViews version 12 application. This study employs secondary data, with a sample of 26 companies selected using the purposive sampling method. The results show that Earnings Quality has an insignificant impact on Firm Value, Meanwhile, Tangible Assets and Leverage have a positive but insignificant impact on Firm Value. So, it can be concluded that tangible asset and leverage are accepted and earnings quality is rejected.